Factors that influence persistence or recurrence of high-grade squamous intraepithelial lesion with positive margins after the loop electrosurgical excision procedure: a retrospective study. Issue 1 (December 2015) - Zhu, Menghan; He, Yuan; Baak, Jan; Zhou, Xianrong; Qu, Yuqing; Sui, Long; Feng, Weiwei; Wang, Qing
Abstract Background In 5–20 % of patients with cervical high-grade squamous intraepithelial lesion (HSIL), a positive margin after the loop electrosurgical excision procedure (LEEP) is associated with persistence/recurrence, but the prognostic value of other clinico-pathological factors is less clear. Methods Among 4336 patients with HSIL who underwent an initial LEEP, 275 (6 %) had HSIL-positive margins, 37 of whom were lost to follow-up. We evaluated the remaining 238 patients. Persistence/recurrence was defined as histopathological HSIL during follow-up. Results The age of the patients ranged from 21 to 69 years (median: 40). The median follow-up period was 25 months (range: 6–43). Of the 238 patients, 211 (88.7 %) patients remained free of persistence/recurrence, while 27 (11.3 %) experienced persistence/recurrence. According to a univariate analysis, age (P = 0.03) and maximum specimen diameter (P = 0.043) were associated with persistence/recurrence, but number/location of involved margin sections and the pathology of the endocervical curettage were not (P > 0.10). The relative risk of the subjects (greater than or equal to 35 years ages) was 4.6 times of the subject less than 35 years, the difference was statistically significant (14 % vs. 3 %, P < 0.05). A multivariate analysis indicated that an age of 35 years or older was the only independent risk factor (OR 4.97, 95 % CI 1.14–21.62, P = 0.03). Conclusion In patients with HSIL and HSIL-involved margins after an initial LEEP, age is a strong independent predictor of persistence/recurrence. Follow-up with screening cytology and/or biopsy may be considered in younger patients, whereas a secondary LEEP/hysterectomy may be considered in older patients.